2018
DOI: 10.1002/nop2.164
|View full text |Cite
|
Sign up to set email alerts
|

Transition from child to adult care in an outpatient clinic for adolescents with juvenile idiopathic arthritis: An inductive qualitative study

Abstract: AimThe aim of this study was to investigate experiences and needs in the transition from child to adult care in an outpatient clinic from the perspective of adolescents with juvenile idiopathic arthritis and their parents focusing on which aspects in the transition could ease the process.DesignA qualitative design with an inductive approach.MethodsInductive content analysis was used to analyse individual interviews with three parents and three adolescents from a rheumatology clinic in Denmark.ResultsThree desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 34 publications
(109 reference statements)
1
2
0
Order By: Relevance
“…The patient experiences shared in this study offer a unique glimpse into the lives of young adults as they navigate two vastly different healthcare systems. This research supports past qualitative findings of significant differences in the model and scope of care between pediatric and adult medical systems that have been identified in other countries [ 17 , 33 , 37 ]. Our findings indicate that this remains an issue in the Canadian context.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The patient experiences shared in this study offer a unique glimpse into the lives of young adults as they navigate two vastly different healthcare systems. This research supports past qualitative findings of significant differences in the model and scope of care between pediatric and adult medical systems that have been identified in other countries [ 17 , 33 , 37 ]. Our findings indicate that this remains an issue in the Canadian context.…”
Section: Discussionsupporting
confidence: 89%
“…Themes and sub-themes identified had support as well in previous qualitative studies as synthesized in a 2020 systematic review which included 16 studies. Preparedness for transition [ 17 , 33 ], readiness for transfer of care [ 17 ], developing self-advocacy skills [ 17 ], continuity and breadth of care [ 17 , 33 ], changing relationships [ 17 ], culture shock [ 17 ], new responsibilities [ 17 ], need for support [ 17 ], social support [ 17 , 34 ], while additional emphases were identified by this study on mental health support and ongoing support needs – beyond the transfer of care. The Kelly et al systematic review [ 17 ] identified support for the whole person (theme of deprived of human focus) which encompasses psychological support, but did not explicitly identify mental health support [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…We know that there are many challenges inherent in the transition process—feeling unprepared, finding new providers, establishing health insurance independently from parents, and becoming more self-reliant in care. 1921 Our post-transfer cohort did report increased difficulties with obtaining insurance, were less likely to have seen a rheumatologist in the past year, and took significantly fewer medications than our pre-transfer group. Difficulties with transfer were reported in nine (23%) post-transfer participants; four of these participants felt these difficulties directly contributed to SLE flare.…”
Section: Discussionmentioning
confidence: 72%